Folklore Ethno-Medicinal Plants Used by the Manger Tribe from Gangtok District of Sikkim-India - Manger, Roshan; Kalita, Jun Moni; Bhutia, Sonam (Pharmacognosy Reviews)
The Manger community, one of the indigenous communities living in Sikkim's Gangtok district since ages, has ethnomedical practices that are examined and documented in this study. Important information on 40 medicinal plant species used to cure a variety of illnesses was gathered through field surveys and interviews with five identified traditional healers. Quantitative analysis was employed using the Informant Consensus Factor (ICF) and Use Value (UV). These plants-mostly herbs (70%)-are used as decoctions, pastes, powders, and liquids. The most commonly used portion is the leaf (27.1%). Asteraceae (11.6%), Apiaceae, and Fabaceae (8.6%) are the most frequently used families. The highest ICF was for respiratory conditions (0.556), and plants like Mentha sylvestris and Costus speciosus (UV=1.0) are highly significant. The findings show how deeply the Manger traditional healers have preserved their cultural knowledge and how urgently thorough recording is needed, especially in light of urbanization and the loss of generational expertise.
Keywords: Folk Medicinal Plants; Gangtok; Manger Tribes; Sikkim; Traditional healers